Fins improve the swimming performance of fish sperm: A hydrodynamic analysis of the Siberian sturgeon Acipenser baerii1. Issue 2 (11th December 2012) - Gillies, Eric A.; Bondarenko, Volodymyr; Cosson, Jacky; Pacey, Allan A.
Abstract The flagella of sturgeon sperm have an ultrastructure comprising paddle‐like fins extending along most of their length. These fins are seen in several other marine and freshwater fish. The sperm of these fish are fast swimmers and are relatively short lived: it is therefore tempting to think of these fins as having evolved for hydrodynamic advantage, but the actual advantage they impart, at such a small length scale and slow speed, is unclear. The phrase "the fins improve hydrodynamic efficiency" is commonly found in biological literature, yet little hydrodynamic analysis has previously been used to support such conjectures. In this paper, we examine various hydrodynamic models of sturgeon sperm and investigate both swimming velocity and energy expenditure. All of the models indicate a modest hydrodynamic advantage of finned sperm, in both straight line swimming speed and a hydrodynamic efficiency measure. We find a hydrodynamic advantage for a flagellum with fins, over one without fins, of the order of 15–20% in straight line propulsive velocity and 10–15% in a hydrodynamic efficiency measure. © 2012 Wiley Periodicals, Inc